Beyond design: Institutionalizing the creative turn in Vietnamese universities - Pham, Quynh Phuong; Phan, Quang Anh; Dao, Manh Dat (Journal of Interdisciplinary Studies in Education, 2026)
Vietnam’s cultural and creative industries (CCIs) policy is among the most explicitly articulated in Southeast Asia, particularly in its delineation of subsectors, GDP-oriented targets, and the strategic role assigned to universities. However, after more than a decade, the formal adoption of CCIs frameworks often appears to outpace substantive operational change. Drawing on neo-institutional theory, especially institutional isomorphism and organizational decoupling, this study analyzes eleven interviews across Hanoi-based higher education institutions alongside national policy documents (2013–2025). The findings indicate that universities respond to reform pressures by adopting formal markers of alignment, while core pedagogical practices remain relatively unchanged, positioning Vietnam as a critical case of policy-driven convergence without equivalent transformation.